Lost in a good game : why we play video games and what they can do for us / Pete Etchells. - Etchells, Pete (Icon, 2019)
When Pete Etchells was 14, his father died from motor neurone disease. In order to cope, he immersed himself in a virtual world - first as an escape, but later to try to understand what had happened. Etchells is now a researcher into the psychological effects of video games. In this, his first book, he journeys through the history and development of video games - from Turing's chess machine to mass multiplayer online games like World of Warcraft - via scientific study, to investigate the highs and lows of playing and get to the bottom of our relationship with games - why we do it, and what they really mean to us. At the same time, 'Lost in a Good Game' is a very unusual memoir of a writer coming to terms with his grief via virtual worlds, as he tries to work out what area of popular culture we should classify games (a relatively new technology) under.